Pain in Older Adults With Dementia: A Survey in Spain - Giménez-Llort, Lydia; Bernal, Maria Luisa; Docking, Rachael; Muntsant-Soria, Aida; Torres-Lista, Virginia; Bulbena, Antoni; Schofield, Patricia A. (Frontiers in Neurology, 2020)
The risk of suffering pain increases significantly throughout life, reaching the highest levels its latest years. Prevalence of pain in nursing homes is estimated to range from 40% to 80% of residents, most of them old adults affected with dementia. It is already known that pain is under-diagnosed and under-treated in patients with severe cognitive impairment and poor/absent verbal communication, resulting in a serious impact on their quality of life, psychosocial and physical functioning. The use of antipsychotics and opioids for pain management is also a topic of current debate. Here, we present two Regional and National Surveys in Spain (2015-2017) on the current practices, use of observational tools for pain assessment, guidelines and policies. Results, discussed as compared to the survey across central/north Europe, confirm the professional concerns on pain in severe dementia, due to poor standardization and lack of guidelines/recommendations. In Spain, observational tools are scarcely used because of their difficulty and low reliability in severe dementia, where the poor/absent verbal communication and comprehension are considered limiting factors. Behavioural observation tools should be used while attending the patients, in a situation including rest and movement, should be short (3-5 minutes) and scored using a numeric scale. Among the pain items to score, ‘Facial expression’ and ‘Verbalization’ were considered essential and very useful, respectively. This was in contrast to ‘Body movements’ and ‘Vocalizations’, respectively, according to the survey in central/north Europe. The scarce time availability for pain assessment and monitoring confronts to low feasible and time consuming tools, worsening the pain assessment challenge. The presence of confounding factors, the low awareness and poor knowledge/education of specific tools for this population are worrisome. These complains draw the future directions to improve pain assessment. More time available, awareness and involvement of the teams would also benefit pain assessment and management in cognitive impairment. The experiences and opinions recorded in these surveys in Spain and other EU countries were considered as sources of knowledge for the design of ‘PAIC-15 scale’, a new internationally agreed‐on meta‐tool for Pain Assessment in Impaired Cognition and the ‘Observational pain assessment in older persons with dementia.